Bioremediation a potential approach for soil contaminated with polycyclic aromatic hydrocarbons: An Overview - Othman, Norzila; Juki, Mohd Irwan; Hussain, Norhana; Abdul Talib, Suhaimi (International Journal of Sustainable Construction Engineering and Technology, 2011)
Polycyclic aromatic hydrocarbons (PAHs) represent a group of priority pollutants which are present at high concentration in soils of many industrially contaminated sites. Standards and criteria for the remediation of soils contaminated with PAHs vary widely between countries. Bioremediation has gained preference as a technology for remediation contaminated sites as it is less expensive and more environmental friendly. Bioremediation utilizes microorganisms to degrade PAHs to less toxic compounds. This technology degrades contaminants through natural biodegradation mechanisms or enhanced biodegradation mechanism and can be performed in-situ or ex-situ under aerobic or anaerobic conditions. The purpose of this paper is to highlight potential of using isolated strains from municipal sludge on soil remediation. Several indigenous bacteria from municipal sludge namely genus Micrococus, Sphingomonas, and Corynebacterium demonstrated a high removal rate of PAHs with more than 80% of lower molecular weight of PAHs degraded after one week incubation. Laboratory studies had established that these genus able to degrade PAHs on contaminated soil. The successful application of bacteria to the bioremediation of PAHs contaminated sites requires a deeper understanding of how microbial PAH degradation proceeds. An overview of research focusing on biodegradation of PAHs will be presented.